The IMF Monetary Model At Forty - Polak, J. (IMF Working Papers; Working Paper ;, 1997)
A model reflecting the monetary approach to the balance of payments was developed in the International Monetary Fund (IMF) in the 1950s. Its purpose was to integrate monetary, income, and balance of payments analysis, and it became the basis of the conditionality applied to IMF credits. Extremely simple, with primary focus on the balance of payments effects of credit creation by the banking system, the model has retained its usefulness for policy purposes over time, as it was adapted to changes in member countries' priorities and in the international monetary system, in particular the disappearance of the par value system.